Analysis of Vibration Characteristic of End- block Type Ball Screw Pair - Chen Yongjiang; Tang Wencheng (Jixie chuandong)
In order to investigate the vibration characteristic of ball screws,an end- block type ball screw is selected as an example,a vibration model of the ball screw which is capable of capturing the vibration in drive dynamics as the nut moves along the screw is established. Based on the stiffness and damping stiffness which considering the nut raceway and screw raceway contact interface lubrication,hybrid model of flexible ball screw is established. Then,the vibration data are collected and analyzed on the test bench of ball screw vibration and noise. Finally,the effect of varying the screw rotational speed and nut position on the ball screw vibration are investigated numerically and experimentally. The analysis indicates that the movable nut plays the role of supporting spring in the ball screw feed drive,therefore,the vibration of the ball screw is very sensitive to nut position changes.